PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL TERHADAP PENDAFTARAN DAN TRANSAKSI KARYA NON-FUNGIBLE TOKEN YANG BUKAN OLEH PEMILIK HAK CIPTA - Aaron Bryant Korengkeng (Gapenas Publisher, 2023)
Non-Fungible Tokens, or NFTs as they are commonly referred to, are digital certificates that attempt to give verification of specific assets in the field of cryptographic art, where the certificate serves as evidence of ownership of an original digital artwork. This study seeks to identify the factors that influence the impact and repercussions of Non-Fungible Token (NFT) registration and transactions that are not conducted by copyright holders, as well as their legal protection, and to determine whether NFTs are a viable option for protecting intellectual property rights in the digital world. This study employs normative legal research with conceptual, statutory, and case-based methodologies. This research also demonstrates that there is no exact and accurate legal regulation of Non-Fungible Token digital works, and that the Law on Copyright is the most applicable law that can be utilized temporarily until new regulations are enacted to govern this. Cryptography, particularly Non-Fungible Tokens, has a very broad and long-term potential, and it is inevitable that it will become one of the solutions to copyright protection, as Non-Fungible Tokens contain a certificate of authentication of a work, a certificate of proof of ownership, and a history of ownership of the work. Even though there is no legislation governing it, the work in the form of Non-Fungible Tokens should be an original work that is not the result of identity theft or theft of all or part of the composition of a work